Experimental study on heaving plate type wave energy converter in front of vertical seawall - Muhammad Ridhuwan Jaafar (2014)
In the present study, in order to investigate the feasibility of a novel heaving plate wave energy converter installed in front of vertical seawalls to protect the coastal structure while generating power, a model is utilized to determine interactions developed between in types of waves. The purpose of the experiment is to determine the wave terminating effects of the model by the reflection coefficient of the model and its ability to harness the wave energy. The experimental tests were carried out in a wave flume simulating 9 different characteristics set of waves. Resolution wave separation technique was employed to determine the reflection coefficient of the model set-up. Video graphics analysis was done to determine the heaving plate activity. The study finds that the model was successful in reducing the reflection coefficient. As for the heaving plate activity, the tests show that the heaving plate motion does not correlate with wave energy damping action. Therefore the experimental study proves that the heaving plate model is effective in reducing the reflection coefficient of the seawall but wave energy harnessing are restricted to certain wave characteristics. The study suggests that the model be tested with different damping strength and also improvements in the design to be made for higher consistency in heaving motion of the model. The study also suggests for particle kinetics beneath the heaving plate to be further explored.